Does Inflation Affect Economic Growth? A case of Turkey and U.S. - Canakci, Mehmet (International Journal of Economics and Financial Issues, 2021)
Understanding the interaction between growth and inflation is at the top of the macroeconomic problems. Whether inflation has an impact on growth has been debated for many years in economics literature. The content of these discussions has changed depending on the period of the world economy. For this reason, indicators such as inflation, fixed capital formation, and labor force values are among the basic indicators affecting the economic growth rate of a country. Therefore, this research aims to examine the effects of inflation on economic growth in the US and Turkey. The time-series data analysis is conducted and the data is collected from the world development indicators by the World Bank. Gross domestic product is a dependent variable as a proxy of growth and development and consumer price index is an independent variable as a proxy of inflation. The data cover the period from 1990 to 2019, and the results from empirical analysis show that inflation does not have a significant effect on GDP in the long run for both countries, but is effective in the short run. The results of this study can provide an estimate of how effective the inflation factor of developed or developing countries can be. Keywords: Inflation, Gross Domestic Product, Cobb Douglas Production Function, ARDL JEL Classifications : E31, E01,O47,E23 DOI: https://doi.org/10.32479/ijefi.11379